2016
DOI: 10.1111/1440-1681.12662
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continuous positive airway pressure on heart rate variability during the night in patients with chronic heart failure and central sleep apnoea

Abstract: Continuous positive airway pressure (CPAP) improves autonomic activity in patients with chronic heart failure (CHF) and central sleep apnoea (CSA), but its effect on heart rate variability (HRV) during therapy has not been reported. We hypothesized that CPAP may decrease HRV, despite its beneficial effects on sympathetic overactivation, due to the expected stabilization of breathing. Sixty-seven CHF patients underwent polysomnography (PSG). Ten of them presented with CSA (age 66.1±8.5 years, apnoea-hypopnea in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…While the exact significance and clinical relevance of this finding is unclear, some potential insight can be drawn from the adult literature. For instance, Terziyski et al studied the acute, short‐term effects of NCPAP on HRV parameters in adults with chronic heart failure and central sleep apnea. They found that time domain HRV parameters were significantly lower with the application of NCPAP, and suggested that these changes were best explained by reduction of the apnea‐hypopnea index and stabilization of the breathing pattern.…”
Section: Discussionsupporting
confidence: 90%
“…While the exact significance and clinical relevance of this finding is unclear, some potential insight can be drawn from the adult literature. For instance, Terziyski et al studied the acute, short‐term effects of NCPAP on HRV parameters in adults with chronic heart failure and central sleep apnea. They found that time domain HRV parameters were significantly lower with the application of NCPAP, and suggested that these changes were best explained by reduction of the apnea‐hypopnea index and stabilization of the breathing pattern.…”
Section: Discussionsupporting
confidence: 90%
“…In CHF, markedly reduced HRV has been demonstrated to coincide with the severity of CHF, as well as being an independent marker of sympatho-excitation. On the other hand, after acute myocardial infarction, depressed HRV predicts cardiac mortality and malignant arrhythmias [ 103 , 104 ]. In 2007 Kiviniemi et al [ 105 ].…”
Section: Heart Rate (Hr) and Hr Variability (Hrv)mentioning
confidence: 99%
“…Cardiac autonomic dysfunction can be measured noninvasively using heart rate variability (HRV) (Hillebrand et al, 2013). Many studies have Trinh et al 10.3389/fnins.2023.1116154 shown that chronic low HRV values are associated with sudden cardiac death while reduction of HR and increase of HF can be considered a beneficial direction for cardiovascular diseases (Haarala et al, 2011;Terziyski et al, 2016;Sessa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%